C. Louis Leipoldt se bydrae tot die materiaalversameling van J.J. Smith se Afrikaanse standaardwoordeboek - du Plessis, J.C.M.D. (Lexikos, 2022)
C. Louis Leipoldt’s Contribution to the Collection of Materials for J.J. Smith’s Afrikaans Standard Dictionary. The friendship between Smith and Leipoldt originated during their years of study in London. This led to Leipoldt showing some of his poems to Smith. Oom Gert vertel en ander gedigte with an introduction by Smith was the first poetry collection by Leipoldt. Subsequent collections of his were linguistically edited by Smith. J.C. Kannemeyer writes extensively about this in his biography of Leipoldt. When Smith started with the collection of materials for the Afrikaans standard dictionary, Leipoldt on a smaller scale made contributions with the elucidation of plant and animal names, and folk medicine. This article discusses a representative collection of this material with regard to kind, method, etc. Keywords: Afrikaans standard dictionary, plant names, animal names, folk medicine